The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.physbeh.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological evidence for attention bias to food, emotional dysregulation, disinhibition and deficient somatosensory awareness in obesity with binge eating disorder

Abstract: Food images elicited neural activity indicating attention bias (cuneate & PCG), emotion dysregulation (BA 19 & 32), and disinhibition (MFG, BA6 & SFG) in obese with BED. These may help tailor a treatment for the obesity with BED phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
(59 reference statements)
2
25
1
Order By: Relevance
“…Finally, our exploratory analyses revealed that stronger baseline FC in the DMN and FPN was associated with enhanced cognitive control of eating behavior after surgery. Presurgery FC of the hippocampus with lingual gyrus (involved in food cue processing) and precentral gyrus was positively associated with reduced eating in response to emotions and external cues after surgery. The PCC coordinates internally directed attention , while the precuneus is involved in self‐centered mental imagery and consciousness or awareness .…”
Section: Discussionmentioning
confidence: 96%
“…Finally, our exploratory analyses revealed that stronger baseline FC in the DMN and FPN was associated with enhanced cognitive control of eating behavior after surgery. Presurgery FC of the hippocampus with lingual gyrus (involved in food cue processing) and precentral gyrus was positively associated with reduced eating in response to emotions and external cues after surgery. The PCC coordinates internally directed attention , while the precuneus is involved in self‐centered mental imagery and consciousness or awareness .…”
Section: Discussionmentioning
confidence: 96%
“…Anorexia nervosa (AN) is recognized as a severe mental disorder characterized by restrained eating, dysfunctional thoughts, preoccupation concerning food and body image disturbance [1,2]. In addition to maladaptive cognitions and behaviours, difficulties in emotion regulation and food craving regulation have been linked to disordered eating symptomatology (i.e., binging, purging, or restriction), which are considered to be contributing factors to the maintenance of eating disorders [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Converging data using different methodologies, such as brain imaging, eye tracking and behavioural test paradigms37 have found that patients with BED demonstrate a higher arousal rate in response to food stimuli, a concurrent motor plan to start eating, a higher reward sensitivity and greater inhibitory deficits as compared with individuals without BED 32 38 39. Those with obesity and BED (compared with obesity alone) have demonstrated that their attentional bias to food images held higher motivational value,40 and responded more to high calorie food images in sites of cognitive planning of motor movements, driven by emotions, which may reflect impulsive tendencies in the face of a binge-eating trigger. This tendency to approach and consume palatable food items may thus be compounded by a greater sensitivity to reward and a decreased capacity to inhibit action tendencies.…”
Section: Introductionmentioning
confidence: 99%